SELEBRASI PERNIKAHAN ARTIS DALAM PERSPEKTIF TEORI MASYARAKAT KONSUMSI BAUDRILLARD - Sholahudin, Umar (Journal of Urban Sociology, 2019)
Globalization and modernization have given birth to a consumption society. Individuals or groups of people expressively celebrate excessive consumption. One of the celebratory phenomena of overconsumption in our society is marriage among artists; Rafii-Gigi's wedding. A marriage that contains values of piety and religiosity, is reduced to a celebration of the consumption of goods and services filled with signs. A sign to gain social image and prestige. How these social phenomena are read analytically by sociological theory; Baudrillard theory of consumption society. This research is a qualitative research using literature method. Data and information collected from the mass media and facts that occur. The results showed, the existence of a person is determined by what goods or commodities are consumed. Self-existence is no longer determined by the way and how the individual thinks, but what and how the individual produces as much image and priority as possible. The super luxurious celebration of Raffi-Gigi's wedding and being a social magnet is a reflection of the moderation of a consumption society that is devoid of public morality. Show of "permissibility" is the right of every individual, but it is necessary to remember also not to show luxury and glamor to destroy the sensitivity and human values.Â Key Word :Celebrations, Artist Weddings, Society Consumption Theory